Design, implementation, and evaluation of self-care program in the prevention of breast cancer among women in Isfahan: a community-based participatory action research protocol - Maryam Kianpour; Fariba Taleghani; Mahnaz Noroozi; Mitra Savabi-Esfahani; Zahra Boroumandfar; Tahereh Changiz; Zahra Ravankhah; Shaghayegh Haghjooy Javanmard; Maryam Sadat Hashemi (BMC, 2022)
Abstract Introduction Breast cancer is one of the most prevalent cancers among women in Isfahan, Iran; however, its prevention is not desirable in this city. This disease poses several health, social and economic challenges for women. To promote women's self-care in breast cancer prevention, this study aims to design, implement and evaluate a self-care program among women in Isfahan through using a community-based participatory action research method. Methods The present study is based on a community-based participatory action research approach. In this study, the participatory action research includes four general phases of organizing, action planning, action, and rethinking. These phases are summarized as follows: In the organizing phase, the needs of the participants and the action research settings are examined. This means that the current situation is identified and the views of the process owners are assessed. In the action planning phase, using the results of the first phase, some strategies are designed to promote self-care behaviors in the prevention of breast cancer among women in Isfahan. In the implementation phase, the selected strategies are implemented with the help of the process owners. Finally, in the rethinking phase, the results of the implementation of the strategies are monitored and evaluated. This cycle continues until the intended results are achieved. Discussion Changing the role of individuals from a passive status to an aware and active status in the care process requires motivation, responsibility, and active participation of individuals in the disease control process. Moreover, many cultural and social factors affect the active participation of Iranian women. Therefore, individuals can be involved in promoting their health using a community-based participatory action research approach.